2018
DOI: 10.1111/clr.13338
|View full text |Cite
|
Sign up to set email alerts
|

Is there an effect of crown‐to‐implant ratio on implant treatment outcomes? A systematic review

Abstract: ObjectivesHigh crown‐to‐implant ratios may lead to complications due to unfavorable occlusal forces, including nonaxial forces, on the bone surrounding the neck of the implant and within the connection of the crown and implant itself. The aim of this study was to perform a systematic review on the influence of crown‐to‐implant ratio of single‐tooth, nonsplinted, implants on biological and technical complications.Materials and Methods MEDLINE (1950–January 2018), EMBASE (1966–January 2018), and Cochrane Central… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 29 publications
3
40
0
2
Order By: Relevance
“…While the present study showed that crown‐to‐implant ratio had an impact on radiopacity, a recently published analysis tested for a possible effect of crown‐to‐implant ratio on the marginal bone level but did not prove any clinical impact (Guljé, Raghoebar, Erkens, & Meijer, ). Within a range of 0.86–2.14 (thereby covering the ratios for both test and control implants of the present analysis), the crown‐to‐implant ratio seems not to have an effect on biological or technical complications (Meijer, Boven, Delli, & Raghoebar, ). Any clinical relevance of the difference in GSV after 5 years of loading therefore appears to be questionable.…”
Section: Discussionmentioning
confidence: 85%
“…While the present study showed that crown‐to‐implant ratio had an impact on radiopacity, a recently published analysis tested for a possible effect of crown‐to‐implant ratio on the marginal bone level but did not prove any clinical impact (Guljé, Raghoebar, Erkens, & Meijer, ). Within a range of 0.86–2.14 (thereby covering the ratios for both test and control implants of the present analysis), the crown‐to‐implant ratio seems not to have an effect on biological or technical complications (Meijer, Boven, Delli, & Raghoebar, ). Any clinical relevance of the difference in GSV after 5 years of loading therefore appears to be questionable.…”
Section: Discussionmentioning
confidence: 85%
“…It should also be mentioned that in vitro studies have shown that splinted implants provide better distribution of high occlusal forces despite the unfavorable crown-to-implant ratio [52]. A systematic review by Meijer et al showed that with splinted implant-supported restorations, the connection between crown and implant may behave differently, perhaps transmitting forces onto peri-implant bone of a different magnitude from non-splinted restorations [53]. In the present study, crestal bone stability was measured by radiographic examination at the time of implant placement, and 2, 6, 12, and 24 months after.…”
Section: Discussionmentioning
confidence: 99%
“…The meta-analysis on nonsplinted implant-supported singletooth restorations with increased crown-to-implant ratio after a mean observation time ranging from 12 to 74 months including eight studies demonstrated high survival rates of the implants and small mean marginal bone loss (Meijer, Boven & Raghoebar, 2018). Scarce evidence could be retrieved on whether different increased crown-to-implant ratios have an influence on the former outcomes.…”
Section: Major Findings From the Reviewmentioning
confidence: 99%